A Librarian's Experience Teaching Critical Information Literacy. Issue 2 (6th September 2022) - Ward, Latia
Abstract: Information literacy focuses on knowing how to use information for work and civic duties, however, critical information literacy goes a step further to recognize that a source's good reputation does not mean that the source is accurate or unbiased. Critical information literacy questions the motives of the systems that produce the information and includes the knowledge of students so that they influence the lesson as well. Librarians have made critical information literacy a part of their lessons in a variety of ways, and teaching critical information literacy is rooted in critical pedagogy. A review of the literature on critical information literacy and a discussion of the American Association of College and Research Libraries' framework "Authority Is Constructed and Contextual" in a critical information literacy lesson in an advanced legal research class is considered.